Faktor-Faktor yang Mempengaruhi Keputusan Pembelian Online Pada E-Commerce Shopee Pasca Pandemi Covid-19: Studi Empiris di Kota Banda Aceh - Muhammad Arif Mufti; Nilam Sari; Muhammad Zulhilmi (Jurnal Ekonomi Manajemen dan Sekretari, 2024)
This research uses quantitative methods by obtaining data sources from primary and secondary data. This study aims to determine how the effect of price, trust and security on online purchasing decisions on Shopee e-commerce after the covid-19 pandemic. The population in this study were the people of Banda Aceh City with a sample of 100 respondents using the purposive sampling technique formula. The data analysis method uses the multiple linear regression using the help of SPSS software. The research results obtained show that the price, trust and security variables simultaneously have a positive and significant effect on purchasing decisions. Partially, each variable, namely price, trust and security, has a positive and significant effect on purchasing decisions.